CONFLICT, MIMETIC RIVALRY AND NONVIOLENCE: FRIENDSHIP AS AN ETHICAL HORIZON OF COEXISTENCE - Soares Junior, Antonio Coêlho; de Souza Junior, Joaquim Ribeiro; Pereira, Mariana Maria (Seven Editora, 2026)
This article examines, from a philosophical perspective, the status of conflict in human relations and investigates to what extent nonviolence can interrupt the mimetic logic that turns difference into hostility. It begins from the hypothesis that conflict belongs to the relational condition of the human being and therefore cannot simply be eliminated from social life. The problem emerges when conflict is captured by violent reciprocity and rivalry, producing forms of enmity that degrade the bond with the other. Based on bibliographical research with a qualitative and theoretical-conceptual approach, the text brings into dialogue Jean-Marie Muller, René Girard, Georg Simmel, Zygmunt Bauman, Norberto Bobbio, José Maria da Silva Rosa, and Leo Tolstoy. It argues that nonviolence does not mean passivity, but an ethical practice of resisting violence without reproducing it. The article concludes that friendship may be understood as an ethical horizon of coexistence, since it allows one to think relations shaped by responsibility, recognition, and the refusal of revenge.